Análisis y elaboración de una base de datos realizada según el censo de equipos electrónicos para el uso médico del hospital Guayaquil “Dr. abel gilbert pontón - Real Rojas, Julio Manuel (2009)
This topic has two main objectives: The first objective is to realize a poll to the Administrator and the Maintenance Manager of the Hospital Guayaquil “Dr. Abel Gilbert Pontón” and the second objective is to develop a database of the hospital equipment. This topic consists in two parts. The first one, consist of a poll made to the Administrator and the Chief of the Maintenance Department of the Hospital Guayaquil “Dr. Abel Gilbert Pontón”. A poll with a great importance because it will provide the necessary information about the level of medical attention given by this institution, which takes as reference standards, codes and policies in the areas of electrical, mechanical, environmental, electromagnetic, biological and radioactive safety. The second part consists in the elaboration of a poll about the medical equipment that the institution have. The information obtained will not only provide the level of equipment of the Hospital but will also be useful to let the community know about the kinds of services that they will be able to obtain. This poll is also used to determine the causes for which, electronic equipment for medical use, are damaged.